New Tuberculosis Vaccine Strategies: Taking Aim at Un-Natural Immunity. Issue 5 (May 2018) - Jeyanathan, Mangalakumari; Yao, Yushi; Afkhami, Sam; Smaill, Fiona; Xing, Zhou
Abstract : Despite some major progress made in developing tuberculosis (TB) vaccine strategies, with a dozen novel vaccines currently in the clinical pipeline, the world is still missing an effective TB vaccine. This questions whether any major breakthroughs can be achieved without making a drastic departure from the current strategy, which creates a state of 'near-natural immunity', imitating the natural immunity developed after Mycobacterium tuberculosis ( Mtb ) infection. Here, we argue instead that mounting evidence suggests an effective strategy ought to induce a state of all-around 'un-natural' immunity comprising trained innate immunity (TII), tissue-resident memory T cells (TRM ), and anti- Mtb surface antibodies in the lung. Thus, here we summarize the latest information, thinking, and development in the field of TB and vaccines. Highlights: The world still does not have an effective TB vaccine. Recent efficacy vaccine trials, regardless of unfavorable outcomes, have provided valuable knowledge for future trials. Vaccine-TII has an important protective role. Properly designed respiratory mucosal (RM) vaccination induces lung TII, which overcomes Mtb -imposed innate immune suppression and restrains Mtb growth. Mtb infection slows down the migration of circulating T cells to the lung. Localization of vaccine-induced T cell immunity at the site of infection is critical to the early control of Mtb . RM vaccination can also effectively induce the generation of lung tissue-resident TRM . Quality antibodies, particularly those against Mtb surface glycolipids, correlate with protection. Effective vaccines also need to trigger such antibody responses in addition to TII and T cell immunity.